A Note on Child Policy and Fertility in an Overlapping Generations Small Open Economy: When the Labour Market Institutions Matter. (29th August 2012) - Fanti, Luciano; Gori, Luca
Abstract : We examine how fertility reacts to the public provision of child allowances in a small open economy with overlapping generations. When the labour market is competitive, we find that a child allowance policy acts as a fertility-enhancing device. In contrast, when the labour market is unionised the child policy may be ineffective.